Derepression of a mouse alpha-fetoprotein expression vector in COS-1 cells by amplification of specific cis-acting sequences of the AFP promoter. - Rabek, J P (1990)
The existence of trans-acting regulatory factors has been demonstrated by in vivo competition with cis-acting sequences from both viral and eukaryotic genomes. Plasmids containing a functional SV40 origin of replication when transfected into permissive SV40 T-antigen producing COS-1 cells will amplify to high copy numbers (5,000 to 10,000) without inflicting toxic effects upon the host cell. This amplification vector (pSVori) has been used to amplify cis-acting regulatory elements which can act as competitors for positive and negative trans-acting factors in vivo. Using this amplification system we conducted experiments to determine whether amplification of alpha-fetoprotein (AFP) and albumin cis-acting promoter sequences could activate a corresponding co-transfected AFP-promoter-CAT or Alb-promoter-CAT expression vector in COS-1 cells. We used pMoMLV(-1009)AFPcat, or p(-308)Albcat-MoMLV as reporter genes and pSVori to amplify specific promoter sequences of the AFP or albumin promoter. Our experiments indicated that amplification of a region from -53 to -202 of the AFP promoter resulted in the activation of the pMoMLV(-1009)AFPcat and p(-308)Albcat-MoMLV expression vectors in COS-1 cells. Surprisingly, amplification of the albumin promoter sequences failed to activate either the pMoMLV(-1009)AFPcat or p(-308)Albcat-MoMLV plasmids.